HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KEPATUHAN PENATALAKSANAAN DIET LANSIA DENGAN HIPERTENSI DI LINGKUNGAN KELURAHAN TONJA - Dewi, Kadek Cita Citra; Prapti, Ni Ketut Guru; Saputra, I Kadek (Coping: Community of Publishing in Nursing; Vol 4 No 1 (2016): APRIL 2016, 2016)
Elderly has high risk of suffering from degenerative diseases, such as hypertension. From the interview result with eight of ten elderly in Tonja who have hypertension said their blood pressure often increases because of their disobedient diet. This happens due to lack of family support in organize food that can be consumed by the elderly with hypertension. This study aims to determine the relationship of family support on adherence to the dietary management of elderly with hypertension in Tonja North Denpasar. This is an observational study with cross sectional approach. The sample in this study amounted to 40 respondents with total sampling technique. Instrument used of a questionnaire about family support and compliance with dietary management. Spearman rank correlation test results get the value of p = 0.000, which means p <0.05 and showing values ??(r) 0.849, which means there is a very strong relationship between the variables of family support with the level of compliance with dietary management (range from 0.80 to 1.000). From the results of these studies are expected health workers in providing health services should always involve the patient's family, especially in implementing the diet.
Keywords: Elderly, Hypertension, Family Support, Adherence to Dietary Management.